Never as fast or as big as this - Corominas Botana, David (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
This paper sets out several communication and strategic features of Podemos’ success as a challenging proposition to the Spanish establishment: success in the European elections and in the opinion polls to gauge voting intention. It looks at the capacity of Podemos to put its finger on society’s pulse, to capture the deepest insights of Spanish citizens, and to convert triumphantly the masses into electoral arms while cementing a political organization, which has quite simply kept expanding month after month. Its argument is based on an overview of three cases of electoral success involving political choices that go against the hegemonic powers in their own countries: Syriza in Greece 2015, M5S in Italy 2013 and Obama in USA 2008. It discusses  differences and similarities, but above all  it will note the most distinctive element  of Podemos: a combination of speed of its rise and the extent of  its support
Keywords: Podemos; Syriza; M5S; Obama; Beppe Grillo; social insight; politiCAL discourse; hegemony; establishment